2011
DOI: 10.1128/jb.01158-10
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Thirteen Isolates of Borrelia burgdorferi

Abstract: Borrelia burgdorferi is a causative agent of Lyme disease in North America and Eurasia. The first complete genome sequence of B. burgdorferi strain 31, available for more than a decade, has assisted research on the pathogenesis of Lyme disease. Because a single genome sequence is not sufficient to understand the relationship between genotypic and geographic variation and disease phenotype, we determined the whole-genome sequences of 13 additional B. burgdorferi isolates that span the range of natural variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 23 publications
4
130
0
Order By: Relevance
“…genomes and focused on the comparison of 14 conspecific genomes of the genospecies B. burgdorferi sensu stricto (B. burgdorferi s.s.) (Table 1) (Fraser et al 1997;Casjens et al 2000Casjens et al , 2011aCasjens et al , 2011bGlockner et al 2004Glockner et al , 2006Schutzer et al 2011). Ten of the B. burgdorferi s.s. genomes were from sympatric isolates from the northeastern United States (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…genomes and focused on the comparison of 14 conspecific genomes of the genospecies B. burgdorferi sensu stricto (B. burgdorferi s.s.) (Table 1) (Fraser et al 1997;Casjens et al 2000Casjens et al , 2011aCasjens et al , 2011bGlockner et al 2004Glockner et al , 2006Schutzer et al 2011). Ten of the B. burgdorferi s.s. genomes were from sympatric isolates from the northeastern United States (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…nov. are also frequent causes of this disease (9). To date, whole-genome sequences have been reported from 14 B. burgdorferi sensu stricto isolates (2,5,13) and one unnamed sensu lato species (3), and the chromosome and incomplete plasmid sequences have been reported for one B. afzelii and one B. bavariensis sp. nov. isolate (6,7).…”
mentioning
confidence: 99%
“…The results indicated that bb0844 is located on a smaller replicon, most likely on a linear plasmid of 25 to 28 kbp, rather than on the chromosome (data not shown). Genomic sequences of several B. burgdorferi strains have recently been reported (40). BLAST analysis revealed a sequence with Ͼ99% identity to bb0844 on plasmid lp28-1 of strain WI91-23.…”
Section: Resultsmentioning
confidence: 99%
“…OspC types A, B, C, and K have the largest chromosomes, as indicated in the current study by the presence of bb0852. B31, a typical OspC type A strain, contains an extra 8.5 kbp at the right chromosomal end; Sh-2-82 and JD1, OspC types K and C, respectively, have chromosomes which are approximately 12 kbp longer than that of B31 (40). The chromosomes of Sh-2-82 and JD1 have not been sequenced, and thus, the precise nature of the right chromosomal ends in these strains beyond that of B31 is not currently known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation